A Benford Analysis of National Collegiate Athletic Association Division I Finance Data. (April 2020) - Jones, Willis A.
The Equity in Athletics Disclosure Act (EADA) database and the USA Today NCAA athletics department finance database are two of the most commonly used databases for scholars, policy makers, and other constituents interested in studying the economics of college athletics. Many in the higher education community, however, question the validity of these databases. This study used Benford's Law of First Digits as a tool for spotting irregularities in EADA and USA Today college athletics financial data. After reviewing 5 years of data, the findings show that while there was some slight deviation from Benford's Law, EADA and USA Today data largely conformed to the expectations of Benford's Law.